Distance measurements and limitations based on guided wave 24 GHz dual tone Six-port radar. Issue 3 (25th February 2015) - Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Mann, Sebastian; Weigel, Robert; Koelpin, Alexander
Abstract : In the following, a continuous wave radar system based on the Six-port principle will be shown for measurement tasks at enclosed systems needing micrometer accuracy as well as high update rates like tank level monitoring or hydraulic cylinder piston control. To exceed the ambiguity limit of such an interferometric system, a dual tone approach is used. The system will be presented with measurement results at 24 GHz within a WR42 waveguide to prove the feasibility of the proposed concept. Furthermore, considerations on timing will show the potential as a low-latency system, capable of high measurement data update rates, and different influences on the system performance and limitations of such a system will be discussed in comparison to alternative setups.